2009
DOI: 10.1111/j.1654-1103.2009.05314.x
|View full text |Cite
|
Sign up to set email alerts
|

Gradients within gradients: The mesoscale distribution patterns of palms in a central Amazonian forest

Abstract: Questions: What are the relative contributions of environmental factors and geographic distance to palm community structure at the mesoscale, and how do they depend on the length of the environmental gradient covered? How do soil and topography affect variation of the canopy and understory palm community structure at the mesoscale? How does fine‐scale variation within the broad edaphic/topographic classes affect palm community composition? Location: Reserva Ducke, terra‐firme forest, Manaus, Brazil. Methods:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
140
2
7

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(161 citation statements)
references
References 33 publications
12
140
2
7
Order By: Relevance
“…In tropical rainforest, soil clay content has also been shown to affect the distribution of palms (Costa et al, 2009), frogs (Menin et al, 2007), oribatid mites and ants (Oliveira et al, 2009;Vasconcelos et al, 2003;Souza et al, 2007;2016). The effect of each environmental factor varies depending on the scale of analysis (total area surveyed and the number of sampling units).…”
Section: Discussionmentioning
confidence: 99%
“…In tropical rainforest, soil clay content has also been shown to affect the distribution of palms (Costa et al, 2009), frogs (Menin et al, 2007), oribatid mites and ants (Oliveira et al, 2009;Vasconcelos et al, 2003;Souza et al, 2007;2016). The effect of each environmental factor varies depending on the scale of analysis (total area surveyed and the number of sampling units).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the two sympatric Attalea species, A. attaleoides and A. microcarpa are locally segregated in the terra firme forest close to Manaus, A. attaleoides occurs more often on upland plateaus, whereas A. microcarpa is confined to bottomlands (Costa et al 2009). Freitas et al (2012) investigated and found no evidence that seed removal or seed germination patterns in relation to topography or abundance of adults explained the topographic separation between the two species.…”
Section: Discussionmentioning
confidence: 98%
“…Another factor that can be considered favorable to the increase of changes in species composition is the soil type found in plateaus, that is more fertile than the soil of valley and slope areas (Vormisto et al, 2004;Costa et al, 2009), where nutrients leaching in the surface horizons is more intense and constant. Since soil conditions are good in plateau areas, competition by space becomes important.…”
Section: Resultsmentioning
confidence: 99%
“…Most of the studies conducted at Ducke Reserve, near Manaus, are about communities (Tello, 1997;Zuquim et al 2007). In the same area, the species composition of the palm community varied significantly in relation to environmental and geographical gradients (Costa et al, 2009). The distribution of populations of more abundant palm species can be influenced by several components of the forest structure, like litter quantity, canopy opening, tree density, soil types, etc (Cintra et al, 2005).…”
Section: Introductionmentioning
confidence: 99%